In silico-designed peptide targeting MDR1 (P-gp) restores chemosensitivity in colorectal cancer via chitosan nanoparticle delivery - Maden, Hande; Calik, Hilal; Ozturk, Rabia Yilmaz; Yuka, Selcen Ari; Temur, Betul Zehra; Can, Ozge; Doganay, Gizem Dinler; Cakir, Rabia (ELSEVIER, 2026)
Colorectal cancer is the second most common cause of cancer-related deaths worldwide. Most of these deaths are due to failure of chemotherapy caused by drug resistance and resulting tumor recurrence. Therefore, overcoming drug resistance is crucial for the successful treatment of colorectal cancer. In this study, the P5S3 peptide selected by bioinformatics analysis for inhibiting drug resistance and the 5-FU drug were loaded into chitosan nanoparticles and investigated in vitro on drug-resistant colorectal cancer cells. Firstly, P5S3 was identified as a peptide inhibitor by MDR1 binding site-specific molecular docking analyses and in silico prediction of biological and physicochemical properties. The peptide was synthesized using the solid phase synthesis method and characterized by RP-HPLC and LC-MS/MS. Chitosan nanoparticles loaded with 5-FU and P5S3 (5-FU/ P5S3@CSNPs) were synthesized using an ionic gelation method and characterized using a ZetaSizer, FT-IR, FESEM, and UV-Vis. The 5-FU/P5S3@CSNPs were approximately 110 nm in size and spherical in shape, and had a good encapsulation efficiency and loading capacity. Furthermore, drug resistance was conferred to sensitive HCT-116 cells (HCT-116/FU) that were continuously exposed to 5-FU, and the development of drug resistance was confirmed by qPCR. The effect of 5-FU/P5S3@CSNPs on cell viability in HCT-116/FU cells and their inhibitory activities on MDR1 drug efflux pumps were analyzed by XTT and accumulation assay, respectively. Our results demonstrate that the 5-FU/P5S3@CSNPs had high anticancer potential against HCT-116/FU cells and high inhibition ability of MDR1. In conclusion, our findings suggest that 5-FU/P5S3@CSNPs offer a promising approach for the treatment of resistant colorectal cancer.
Keywords: Colorectal cancer; Multidrug resistance; MDR1; Polymeric nanoparticles; Bioinformatics; COLON-CANCER; IN-VITRO; RELEASE; Pharmacology & Pharmacy